Autophagic defects observed in fibroblasts from a patient with β‐propeller protein‐associated neurodegeneration. Issue 12 (29th July 2021) - Lee, Jae‐Hyeok; Nam, Sang Ook; Kim, Eun Kyoung; Shin, Jin‐Hong; Oh, Seung Hwan; Ryu, Dongryeol; Lee, Hye Eun; Mun, Ji Young
Abstract: Beta‐propeller protein‐associated neurodegeneration (BPAN) is associated with mutations in the autophagy gene WDR45 . The aim of this study was to demonstrate autophagic defects in a patient with BPAN. We assayed autophagic markers using western blot analysis and immunocytochemistry and applied transmission electron microscopy (TEM) to visualize the autophagic structures in fibroblasts from a 7‐year‐old Korean female with WDR45 splice‐site mutation (c.977‐1G>A; NM_007075.3). The protein and mRNA expression levels of WDR45 gene were decreased in the patient‐derived fibroblasts. The amount of increase in LC3‐II upon treatment with an autophagy inducer and inhibitor was reduced in mutant cells compared to control cells, suggesting decreased autophagic flux. TEM showed the accumulation of large vacuoles in mutant cells with a decrease of autophagosomes. Our study demonstrated that the WDR45 mutation in this patient impaired autophagy and provided additional insight into ultrastructural changes of autophagic structures.